Char/ash deposition and near-wall segregation in slagging entrained-flow gasification of solid fuels: from experiments to closure equations. (15th March 2020) - Troiano, Maurizio; Solimene, Roberto; Montagnaro, Fabio; Salatino, Piero
Highlights: Closure equations for char/ash deposition and near-wall segregation are derived. Impact experiments of coal and two different biomasses have been considered. Particle impact velocity and carbon conversion influence char and ash deposition. Inelastic rebound is influenced by the structure of particles during gasification. Abstract: The performance of entrained-flow gasifiers of solid fuels is critically affected by the complex gas-solid multiphase flow patterns and near-wall segregation of char/ash particles. The impact-deposition-rebound dynamical patterns of particles, as they approach and collide onto the walls, control the establishment of near-wall segregated phases. A detailed micromechanical analysis of char/ash particles interaction with a surface is considered to characterize ash deposition onto the walls and adhesion and inelastic rebound of char particles. The effect of the residual carbon content within the particles, from char after devolatilization to ash particles, as well as the influence of the impact velocity, have been investigated for different fuels. The experimental outcomes have been used to derive closure equations describing the behaviour of char/ash particles after the collision with the wall, in terms of deposition and inelastic rebound. It has been highlighted that impact velocity and carbon conversion do affect the deposition tendency of char and ash particles, while the inelastic rebound is mainly influenced by the mechanical properties of the bulk of the particles, which are closely dependent on the particle structure developed during the gasification process.